Neonatal gut function, measured by the one hour blood D (+) xylose test: influence of gestational age and size. Issue 2 (February 1980) - Ducker, D A; Hughes, C A; Warren, I; McNeish, A S
Abstract : D(+) Xylose absorption, assessed by one hour blood xylose levels, has been measured after intraduodenal infusion of the sugar in 35 infants of differing gestational age and size. The test was performed between the 2nd and 6th days of life. Full-term appropriately grown infants had higher blood xylose levels (1.41+/-0.07 mmol/l) at one hour than pre-term appropriately grown infants (1.17+/-0.07 mmol/l; P less than 0.05), or 'light for dates' infants, both full-term (0.73+/-0.06 mmol/l; P less than 0.001) and pre-term (0.96+/-0.17 mmol/l; P less than 0.05). Serial studies of 11 infants were made two to five times between the 3rd and 20th day of life. The levels for one hour xylose rose in all groups, but the 'light for dates' infants showed the least rise. There was no sign of catch-up in this group, and some results appeared to fall further behind those of appropriately grown infants. These results suggest that the primal small intestine is maturing in the perinatal period, and that intrauterine growth retardation may impair intestinal absorption. The nutritional significance is not known.